A case report of primary central nervous system lymphoma. Issue 7 (July 2020) - Zeng, Xu; Lu, Xiaofei; Li, Xinlong; Peng, Lilei; Chen, Ligang
Most patients with primary central system lymphoma (PCNSL) have immune dysfunction. PCNSL without immune dysfunction is rare and extremely challenging to diagnose. Here, we report the case of a 52-year-old woman without immune dysfunction who presented with PCNSL. The patient died a few months after diagnosis and during treatment. A review of this PCNSL patient's case highlighted that poor interpretation of imaging features and the poor correlation of laboratory test results with clinical findings led to a difficulty in making a diagnosis and administering the best treatment. For an accurate diagnosis of early stage PCNSL, positron-emission tomography computed tomography and corticosteroids should be used cautiously before stereotactic biopsy.